Impact of Sevoflurane and Thiopental Used Over the Course of Electroconvulsive Therapy: Propensity Score Matching Analysis - Yatomi, Taisuke; Uchida, Takahito; Takamiya, Akihiro; Wada, Masataka; Kudo, Shun; Nakajima, Kazuki; Nishida, Hana; Yamagata, Bun; Mimura, Masaru; Hirano, Jinichi (Frontiers in Human Neuroscience, 2022)
Objective: Although anesthetics play an important role in electroconvulsive therapy (ECT), the clinical efficacy and seizure adequacy of sevoflurane in the course of ECT remain unclear. The purpose of this study was to examine the clinical efficacy and seizure adequacy of sevoflurane, compared to those of thiopental, on the course of ECT in patients with major depressive disorder. Methods: We conducted a retrospective chart review. Patients who underwent a course of ECT and received sevoflurane (n=26) or thiopental (n=26) were included. Factors associated with ECT, and treatment outcomes were compared between the two groups using propensity score (PS) matching. The between-group differences were examined using the independent t-test for continuous variables and χ2 test for categorical variables. Results: Patients that received sevoflurane needed more stimulations (sevoflurane: 13.2 ± 4 times, thiopental: 10.0 ± 2.5 times, df=51, p=0.001) and sessions (sevoflurane: 10.0 ± 2.1 times, thiopental: 8.4 ± 2.1 times, df=51, p=0.01), and had more inadequate seizures (sevoflurane: 5 ± 3.9 times, thiopental: 2.7 ± 2.7 times, df=51, p=0.015). Remission and response rates were similar in both groups. Conclusions: The present findings indicate that sevoflurane should be used with caution in ECT and only when the clinical rationale is clear.